Trade and imperialism in Southern Nigeria 1881-1929 - Ofonagoro, Walter Ibekwe (New York : NOK Publishers International, 1979)
The book gives a vivid account of the history of the Southern Nigeria trade activities during the pre-colonial era. The role played by the Chiefs, the Middle men and as well as the Europeans led by the British government.
Includes index.
Bibliography: p. 409-419.
usc 25/01/2019
Loans
Keywords: Colonial influence; Commerce; Economic history; International economic relations; Nigeria; Great Britain